Soliter Koroid Pleksus Lipomu: BT ve MRG Bulguları - Yıldırım, Hanefi; Murat, Ayşe; Akbaş, Gökhan; Oğur, Erkin (Fırat University, 2004)
Santral sinir sisteminin lipomları son derece nadirdir ve bütün intrakraniyal tümörlerin %0.1'den daha azını oluştururlar. Koroid pleksus lipomu oldukça nadirdir ve çoğunlukla perikallozal lipomlara eşlik ederler. İntrakraniyal lipomlar genellikle asemptomatiktirler. US, BT ve MRG intrakraniyal lipomların tanısı için tercih edilen modalitelerdir. MRG lipomun orjinini, çevre dokularla olan ilişkisini ve lezyonun anatomik lokalizasyonunu göstermede US ve BT'den daha üstündür. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Central nervous system lipomas are extremely rare and constitutes less than 0.1% of all intracranial tumors. Choroid plexus lipoma is a rare pathology too and usually accompanies to pericallosal lipomas. Intracranial lipomas are usually asymptomatic. US, CT and MRI are preferred modalities for diagnosis of intracranial lipomas, MRI is superiorer than US and CT about demonstration of relationship with surrounding tissues, origin of lipoma and showing accurate anatomic localization of lesion. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Solitary Choroid Plexus Lipoma: CT and MRI Findings